2011
DOI: 10.1007/s11695-011-0362-9
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying of Orally Administered Glucose Solutions and Incretin Hormone Responses Are Unaffected by Laparoscopic Adjustable Gastric Banding

Abstract: OGTT can be used to evaluate glucose tolerance in obese patients before and after LAGB without bias from changes in gastric emptying. LAGB has no direct impact on incretin hormone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Six studies have shown that GLP-1 is not increased after medical weight loss and may be decreased (54, 55, 71, 8790). Only 1 of 10 studies in AGB showed an increase in GLP-1, and in that one study it was increased less than RYGB (30); the others showed no change (8, 21, 22, 56, 57, 68, 9193). Every malabsorptive procedure exhibits an increase in GLP-1 (for a discussion of the impact of bile acids on GLP-1, see the section below).…”
Section: Resultsmentioning
confidence: 94%
“…Six studies have shown that GLP-1 is not increased after medical weight loss and may be decreased (54, 55, 71, 8790). Only 1 of 10 studies in AGB showed an increase in GLP-1, and in that one study it was increased less than RYGB (30); the others showed no change (8, 21, 22, 56, 57, 68, 9193). Every malabsorptive procedure exhibits an increase in GLP-1 (for a discussion of the impact of bile acids on GLP-1, see the section below).…”
Section: Resultsmentioning
confidence: 94%
“…However, tracer studies have shown faster exogenous glucose absorption into the systemic circulation after RYGBP compared with AGB, 27 most likely reflecting gastric emptying is accelerated after RYGBP. 28,29 Admittedly, SG has also been associated with accelerated gastric emptying of liquid and semisolid meals. 17 It is tempting to speculate that preservation of the pylorus as in SG-operated subjects would account for the less pronounced postprandrial glycemic peak after this surgical technique compared with RYGBP.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric emptying in individuals with an intact GI tract is tightly regulated [31, 32] due in part to feedback from small intestinal signals activated by luminal nutrients [31]. While gastric banding seems to have no effect on nutrient emptying [33], GB and SG are associated with an increased pace of nutrient passage through the gastric pouch/stomach into the small intestine [34, 35]. Emptying of the stomach pouch in individuals after GB is about 2–3 times faster than that in non-surgical healthy controls for both liquid and solid markers [36].…”
Section: Weight-loss Independent Glycemic Effect Of Bariatric Surgeriesmentioning
confidence: 99%